Electronic Structure and Physical-Chemistry Property Relationship for Oxazole Derivatives by Ab Initio and DFT Methods. (12th September 2011) - Belaidi, Salah; Mellaoui, Malika
Abstract : The geometric, electronic structure, effect of the substitution, and structure physical-chemistry relationship for oxazoles derivatives have been studied by ab initio and DFT theory. In the present work, the calculated values, namely, net charges, bond lengths, dipole moments, electron affinities, heats of formation, and QSAR properties are reported and discussed in terms of the reactivity of oxazole derivatives.